The motif of initiation in selected works by Joseph Conrad - Doherty, Helen (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1998)
This thesis explores the archetypal theme of initiation in selected texts by Joseph Conrad. The Introduction first surveys critical attention to initiatory motifs in Conrad with the objective of demonstrating the need for an approach to the topic informed by a more formal and theorized understanding of initiation. It then offers a prima facie case for the centrality of the idea of initiation in Conrad's oeuvre, based on references culled from a range of the author's writings. Chapter One seeks to contextualise initiation by providing a history of anthropological research into and theorisations of the rite, proceeding to a description of its typical structure and functions. A detailed account is given of the most widely accepted model of initiation, Arnold van Gennep's tripartite schema. Moving on to Conrad's writing, Chapter Two draws on both his fiction and more personal writings in order to provide a provisional account of the writer's own understanding of initiation and its importance, and to offer some explanation of why Conrad should have been prompted to accord the motif such prominence in his work. Conrad's presentation and (impliedly) his understanding of initiation was never entirely consistent and underwent some change in the course of his writing career. The critical assessment of "Typhoon" in Chapter Three depicts Conrad's more optimistic conception of initiation as a rite benefitting both society, by promoting solidarity, and the individual, by advancing self-knowledge. Chapter Four introduces, via analyses of the novellas "Youth" and "The Shadow Line", that variation on the motif of initiation which is more typical of its manifestation in Conrad: the failure of individuals to complete their cycles of initiation. Chapter Five identifies those characteristics of initiation which appear to be determinative in the representations of incomplete initiation in Conrad's work. Initiation seems to play out approximately seven paradoxes; the impact of some of these is examined through analysis of the initiatory ordeals of the main protagonists in The Secret Agent. Integral to this discussion is an attempt to demonstrate the vital role which initiation plays in the healthy maintenance not only of social order but also of faith and life itself. The Conclusion summarises the more important findings of the study and indicates some directions for further, related research.
Keywords: Conrad, Joseph, 1857-1924 -- Criticism and interpretation; Initiation rites in literature